[Notes] (Journal of Political Economy, 1900)
A POLICY of settling disputes quickly and cleanly would allow the disputants one fair trial, ending in a judgment that is absolutely binding on the loser. But there is always a danger that the loser lost because of harmful errors in the proceeding, rather than because he had the poorer case. To prevent judgments in such cases from freezing into finality, two methods of attack-"direct" and "collateral" -are made available to the loser.1 Most errors open a judgment only to direct attack,2 which is usually a continuation of the original action, either as an appeal or through a motion in the rendering court to set aside the judgment.3 In rarer cases a "direct" attack may also be made by an independent equity suit, brought in a different court, to enjoin enforcement of the judgment.4 But whatever the form of the direct attack, the aggrieved party must either have prosecuted his claim promptly or have thoroughly justified his delay.5 In a collateral attack, which may be brought in any court at